Twins induced by high-temperature ion irradiation in body-centered cubic V-4Cr-4Ti alloy. (15th March 2019) - Ding, Jianwen; Yang, Shanwu; Zhu, Boling; Liu, Huiping; Liu, Guoliang; Zhou, Lujun; Zhan, Qian; Wan, Farong
Abstract: V-4Cr-4Ti alloy for future fusion reactors has attracted great interest. In the present study, twins are observed in the V-4Cr-4Ti alloy irradiated with a 500-keV iron ion beam for 2.67 h at 500 °C. The twins are identified as {112} 〈111〉 type. There is no evident composition distinction between the twins and the matrix. Additionally, dense irradiation-induced dislocation loops are observed. It is proposed that coalescence of dislocation loops can facilitate the growth of stacking faults at which the twins nucleate. The mechanism indicates that twinning might be used to absorb irradiation-induced point defects. Graphical abstract: Unlabelled Image